Preference diversity - Matthias Ammann; Clemens Puppe (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2024)
How can we assess the diversity of a group of decision makers? Identifying decision makers with their preferences, we address this question by applying the multi-attribute approach developed by Nehring and Puppe (2002) to sets of preferences. Specifically, we provide a repertoire of alternative models to measure the diversity of sets of preferences. The proposed models are purely ordinal and are characterized in terms of the different properties that a preference order need to satisfy in order to contribute to the diversity of a given set of preference orderings.
Keywords: 330; Diversity; Committees; Sets of Preferences